A sensitive electrochemical sensor for environmental toxicity monitoring based on tungsten disulfide nanosheets/hydroxylated carbon nanotubes nanocomposite. (January 2022) - Wu, Guanlan; Zheng, Huizi; Xing, Yi; Wang, Chengzhi; Yuan, Xing; Zhu, Xiaolin
Abstract: There has been growing concern about the toxic effects of pollutants in the aquatic environment. In this study, a novel cell-based electrochemical sensor was developed to detect the toxicity of contaminants in water samples. A screen-printed carbon electrode, which was low-cost, energy-efficient, and disposable, was modified with tungsten disulfide nanosheets/hydroxylated multi-walled carbon nanotubes (WS2 /MWCNTs-OH) to improve electrocatalytic performance and sensitivity. The surface morphology, structure, and electrochemical property of WS2 /MWCNTs-OH composite film were characterized by emission scanning electron microscopy, transmission electron microscopy, energy dispersive spectroscopy, X-ray diffraction, Raman spectroscopy, and electrochemical impedance spectroscopy. Grass carp kidney cell line was utilized as the sensor biorecognition element to determine the electrochemical signals and evaluate cell viability. The sensor was used to detect the toxicity of one typical contaminant (2, 4, 6-trichlorophenol) and two emerging contaminants (bisphenol AF and polystyrene nanoplastics). The 48 h half inhibitory concentration (IC50 ) values were 169.96 μM, 21.88 μM, and 123.01 μg mL −1, respectively, which were lower than those of conventional MTT assay, indicating the higher sensitivity of the proposed sensor. Furthermore, the practical application of the sensor was evaluated in chemical wastewater samples. This study provides an up-and-coming tool for environmental toxicity monitoring. Graphical abstract: Image 1 Highlights: A sensor based on tungsten disulfide nanosheets/carbon nanotubes was developed. The electrochemical response mechanism of CIK cells was elucidated. The cytotoxicity of 2, 4, 6-TCP, BPAF, and PSNPs was evaluated by the sensor. The sensor exhibited higher sensitivity than traditional MTT assay. The sensor was successfully used to detect toxicity of actual wastewater samples.